Autosomal dominant vitreoretinochoroidopathy (ADVIRC). Issue 1 (January 1984) - Blair, N P; Goldberg, M F; Fishman, G A; Salzano, T
Abstract : We report the second family recognised to have autosomal dominant vitreoretinochoroidopathy. The clinical features were (1) autosomal dominant inheritance; (2) peripheral, coarse pigmentary degeneration of the fundus for 360 degrees, with a relatively discrete posterior border in the equatorial region (this finding may be pathognomonic); (3) superficial punctate yellowish-white opacities in the retina; (4) various vascular abnormalities; (5) breakdown of the blood-retinal barrier; (6) retinal neovascularisation; (7) vitreous abnormalities; and (8) choroidal atrophy. Visual reduction was mainly due to macular oedema or vitreous haemorrhage.